A GIS-based spatio-temporal database approach to land suitability classification for papaya (Carica papaya L.) cultivation - Irawan, Sudra; Sismanto, Sismanto; Sari, Diyan Rahma; Aji, Satriya Bayu (Journal of Degraded and Mining Lands Management, 2026)
Papaya (Carica papaya L.) is a high-value horticultural crop that can be cultivated year-round and helps improve farmers’ incomes. However, successful papaya cultivation depends heavily on environmental conditions, making land suitability assessment a critical step for sustainable development. This study examined the limiting factors influencing the suitability of agricultural land for papaya cultivation on Galang Island using a Geographic Information System (GIS) approach. The study used matching and scoring methods to evaluate land characteristics against papaya growth requirements. The assessment was conducted for each land unit to identify actual and potential land suitability classes based on key environmental parameters. The findings show that land suitability on Galang Island is divided into two categories: actual and potential. Under current conditions, land units 1, 2, and 3 fall into the S3 (marginally suitable) class, with water availability (wa) identified as the primary limiting factor, resulting in an S3wa classification. Improvement measures were proposed to enhance land suitability by increasing the suitability class by one level. The implementation of irrigation systems, improved soil management, and appropriate fertilization is expected to upgrade land units 1, 2, and 3 to the S2 (moderately suitable) class. After improvement, land suitability is classified as S2wa, tc, with water availability and temperature remaining as limiting factors. Some parameters cannot be improved due to inherent natural conditions. Overall, Galang Island demonstrates significant potential for sustainable papaya cultivation.